Homonymous Central Quadrantanopia Caused by an Extrastriate (V2/V3) Infarction: A Case Report - Shu-Fang Lin; Yu-Ting Kuo; Fang-Ling Chang; Rong-Kung Tsai (Kaohsiung Journal of Medical Sciences, 2008)
A 66-year-old Taiwanese aboriginal male had complained of right-side blurred vision for 2 months, especially when reading. He had a 10-year history of hypertension and cardiovascular disease. His best-corrected visual acuity was 20/25 in each eye. Ophthalmoscopy revealed asymmetrical cupping, but a normal disc. Humphrey perimetry showed an upper homonymous para-central quadrantanopic defect. Brain magnetic resonance imaging showed an infarction in the left lower calcarine area over the extrastriate (V2/V3) cortical area and a narrowing of the left middle and posterior cerebral arteries due to severe arteriosclerosis.